TECTONIC AND CLIMATIC CONTROL ON DEPOSITION OF SEEP-CARBONATES: THE CASE OF MIDDLE-LATE MIOCENE SALSOMAGGIORE RIDGE (NORTHERN APENNINES, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
Seep-carbonates are generally related to hydrocarbon seepage on continental margins. Modern cold seeps are abundant in actively deforming tectonic settings, suggesting that tectonics is one of the major controlling factor on fluid emissions. Hydrocarbon seepages areconsidered major geological sources of atmospheric methane, one of the most important green-house gases, and have also been related to climate changes. However, the interplaybetween tectonics and climate change in forcing seepage is not clearly understood. Miocene seep-carbonates, formed in a collisional settingsuch as that ofthe Salsomaggiore area of the Northern Apennines(Italy), provide an opportunitytoassess accumulation and release of methane in response to tectonics and climate change along a convergent margin. Thestudiedseep-carbonatesarerelated to fluid emissions of various intensities coeval with tectonic pulses.Newplanktonic foraminiferal biostratigraphic datareveals thatdepositionof these seep-carbonatesislate Serravallian-early Tortonian in age and partiallycoeval with the Miller’s global cooling event Mi 5 (as used below). These seep-carbonates were deposited in two stages with different seepage modes. During the first stage, local tectonic pulses at the onset of the Mi5 event may have producedslow seepage, whereas during the second stage regional tectonics and more extreme climatic conditions (coolest peak of Mi5 event) may have resulted inafast and more intense seepage as suggested by increasing occurrence of chaotic facies. In the Salsomaggiore Ridge, tectonics and the Mi5 cooling event actively concurredtothe deposition of seep-carbonates in both stages.